Biological response to a bioactive glass coated implant: experimental data - Judas, F (2011)
A biomaterial constituted by a metallic titanium alloy (TiAl6V4) coated with a bioglass layer (Na2O (7-24%), K2O (2-8%), CaO (9-20%), Al2O3 (0.1-2%), MgO (0.1-2%), SiO2 (46-53%) and P2O5 (4-8%) was implanted in the cancellous bone of adult rabbit knee, in orthotopic situation, under conditions of mechanical stability. The animals were sacrificed after 30 (Group I), 90 (Group II), and 180 (Group III) days postoperatively. The bone pieces, containing the samples under investigation, were studied using radiographs, optical microscopy, scanning electron microscopy and electron probe micro-analysis. Radiologically, osteointegration of the implant surface was observed in all cases at the 180th day after the surgery. A new bone formation was observed in the animals of Group I and the specimens observed after 90 days of the surgery (Group II) presented a higher amount of new bone tissue. At the 180th day, the bioglass coating of the metallic titanium alloy was not detected and a total contact between the metallic surface and the new bone tissue was observed. The incorporation of the bioglass layer into the bone matrix occurred without interposition of non mineralized tissues and without the presence of inflammatory cells. These results strongly suggest that the studied ceramic coating material of the metallic implant is bioactive, biocompatible, bioresorbable, and possess osteoconductive properties.